The Impact of Health Education and Healthcare Access on the Quality of Life and Well-being of the Elderly in Indonesia - Anurogo, Dito; Muntasir, Muntasir; Wilanda, Alifah; Andarmoyo, Sulistyo; Sangaji, Joko (Eastasouth Institute, 2024)
This study investigates the impact of health education and healthcare access on the quality of life and well-being of the elderly in Indonesia through a quantitative analysis. A diverse sample of 175 elderly participants was surveyed, capturing demographic information, health education engagement, healthcare accessibility, and subjective well-being assessments. The research employed Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze the complex relationships between the variables. The results revealed significant positive associations between health education, healthcare access, and both quality of life and well-being among the elderly. The study contributes valuable insights for policymakers, healthcare providers, and educators to design targeted interventions to enhance the overall well-being of the elderly in Indonesia.